2016
DOI: 10.1007/s11882-015-0592-3
|View full text |Cite
|
Sign up to set email alerts
|

The Immunologic Mechanisms of Eosinophilic Esophagitis

Abstract: Eosinophilic esophagitis (EoE) is a chronic allergic inflammatory disease that is triggered by food and/or environmental allergens and is characterized by a clinical and pathologic phenotype of progressive esophageal dysfunction due to tissue inflammation and fibrosis. EoE is suspected in patients with painful swallowing, among other symptoms, and is diagnosed by the presence of 15 or more eosinophils per high-power field in one or more of at least four esophageal biopsy specimens. The prevalence of EoE is inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0
9

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(58 citation statements)
references
References 187 publications
1
46
0
9
Order By: Relevance
“…(13) However, there are several lines of experimental and clinical evidence from both animal and human studies to suggest that while IgE-mediated food allergy and EoE both lie on the atopic spectrum, they have distinct pathophysiology. (1416) We have shown that eosinophilic inflammation is independent of both B cells and IgE in animal models.…”
Section: Introductionmentioning
confidence: 99%
“…(13) However, there are several lines of experimental and clinical evidence from both animal and human studies to suggest that while IgE-mediated food allergy and EoE both lie on the atopic spectrum, they have distinct pathophysiology. (1416) We have shown that eosinophilic inflammation is independent of both B cells and IgE in animal models.…”
Section: Introductionmentioning
confidence: 99%
“…Hill and Spergel45 postulated that the prevalence of EoE is increasing and has now reached rates similar to those of other chronic gastrointestinal disorders such as Crohn’s disease. In this survey, the finding that LyE was as frequent as EoE appears to be of particular interest.…”
Section: Discussionmentioning
confidence: 99%
“…EoE features include abdominal pain, painful swallowing (dysphagia) and sometimes food impaction and is more common in males . Inflammation is primarily eosinophilic and is defined by presence of at least 15 eosinophils/HPF in biopsy sections . The EoE transcriptome has been described, with CCL26 (eotaxin‐3), an eosinophil chemoattractant, and MC carboxypeptidase being among the most highly induced genes .…”
Section: Mast Cells and Eosinophils In Allergic Diseasementioning
confidence: 99%